Pectin‐decorated selenium nanoparticles as a nanocarrier of curcumin to achieve enhanced physicochemical and biological properties - Yan Wu; Hong Liu; Zhihua Li; Dongye Huang; Lizheng Nong; Zhengxing Ning; Zhizhong Hu; Chunping Xu; Jing‐Kun Yan (IET Nanobiotechnology)
In this study, the authors developed pectin‐stabilised selenium nanoparticles (pectin‐SeNPs) for curcumin (Cur) encapsulation and evaluated their physicochemical properties and biological activities. Results showed that pectin‐SeNPs and Cur‐loaded pectin‐SeNPs (pectin‐SeNPs@Cur) exhibited monodisperse and homogeneous spherical structures in aqueous solutions with mean particle sizes of ∼61 and ∼119 nm, respectively. Cur was successfully encapsulated into pectin‐SeNPs through hydrogen bonding interactions with an encapsulation efficiency of ∼60.6%, a loading content of ∼7.4%, and a pH‐dependent and controlled drug release in vitro. After encapsulation was completed, pectin‐SeNPs@Cur showed enhanced water solubility (∼500‐fold), dispersibility, and storage stability compared with those of free Cur. Moreover, pectin‐SeNPs@Cur possessed significant free radical scavenging ability and antioxidant capacity in vitro, which were stronger than those of pectin‐SeNPs. Antitumour activity assay in vitro demonstrated that pectin‐SeNPs@Cur could inhibit the growth of HepG2 cells in a concentration‐dependent manner, and the nanocarrier pectin‐SeNPs exhibited a low cytotoxic activity against HepG2 cells. Therefore, the results suggested that pectin‐SeNPs could function as effective nanovectors for the enhancement of the water solubility, stability, and in vitro bioactivities of hydrophobic Cur.